2000
DOI: 10.1046/j.1440-1711.2000.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Tamm-Horsfall protein to complement 1q measured by ELISA and resonant mirror biosensor techniques under various ionic-strength conditions

Abstract: SummaryThe purpose of the present study was to quantify the binding affinity between Tamm-Horsfall protein (THP) and complement 1q (C1q) using ELISA and a resonant mirror biosensor. In ELISA, immobilized THP was incubated with soluble C1q under both low and physiological ionic-strength conditions. Tamm-Horsfall protein bound C1q with an equilibrium dissociation constant (K D ) of 1.9 ± 0.6 nmol/L in low ionic-strength Tris buffers (20 mmol/L NaCl, pH 7.5) and with a lower affinity (K D of 13.4 ± 4.7 nmol/L) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Complement 1q (C1q), the first component of this pathway, binds THP with high affinity. 15,16 These THP/C1q in vitro binding studies correlate with clinical evidence that an interaction between THP and complement may occur in vivo. After liver transplantation, which typically results in complement activation, 17,18 about half of the patients developed renal insufficiency.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Complement 1q (C1q), the first component of this pathway, binds THP with high affinity. 15,16 These THP/C1q in vitro binding studies correlate with clinical evidence that an interaction between THP and complement may occur in vivo. After liver transplantation, which typically results in complement activation, 17,18 about half of the patients developed renal insufficiency.…”
Section: Introductionsupporting
confidence: 62%
“…Tamm-Horsfall protein used in all of the studies in this report was purified from normal human female urine as described previously. 15 One of the tests of classical complement pathway activity that was used to assess the effect of THP on complement activation involved haemolysis of antibody-sensitized sheep RBC (EA). 29 Six concentrations (0.5 to 15 mmol/L) of THP or BSA (Calbiochem, La Jolla, CA, USA) in 0.5 mmol/L MgCl 2 /0.15 mmol/L CaCl 2 (45 mL) were added to 5 mL normal human serum and then were incubated at 37°C for 5 min.…”
Section: Effect Of Thp On Complement Activation -Haemolytic Assaysmentioning
confidence: 99%
“…Since it was first discovered to inhibit viral haemagglutination [33,34], uromodulin has been found to have multiple immune regulatory functions including interactions with neutrophils, monocytes, lymphocytes and myeloid dendritic cells [15][16][17], binding to cytokines and complements, such as IL-1, IL-2, IL-8, TNF-a, C1, C1q and C3 [12][13][14]. In this study, we confirmed that uromodulin bound to immobilized CFH and influenced its function, adding another important factor in complement systems to the family of uromodulin binding proteins.…”
Section: Influence Of Uromodulin-cfh Interaction On C3b Inactivationmentioning
confidence: 99%
“…The affinity of THP for CFH in the ELISA (K D 1 × 10 −6 M ) is about 1000-fold weaker than THP’s binding to C1q which has a K D of 10 −9 M.[19,20] However, the affinity of CFH for THP is similar to the affinity of CFH for its normal ligand, C3b, which has been reported with a K D of 10 −8 M to a K D of 10 −6 M.[34,35] Another group recently published results similar to ours showing that THP/uromodulin bound to CFH using surface plasmon resonance (K D = 4 × 10 −6 M). [36]…”
Section: Discussionmentioning
confidence: 99%
“…THP binds strongly to complement 1q (C1q), a key initiating protein in the classical complement pathway, and appears to prevent activation of this pathway. [19,20,21] Several in vivo studies suggest a linkage between THP and renal complement inhibition. Complement activation occurs during ischemia-reperfusion injury (IRI)[22,23] and organ transplantation.…”
Section: Introductionmentioning
confidence: 99%